2022
DOI: 10.1017/s1047951122003390
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function in adults with Fontan palliation versus acyanotic CHD patients and association with health-related quality of life

Abstract: Background: Impairments and developmental delay are often reported in infants and young children with CHD. However, currently, there is no data regarding cognitive abilities assessed by standardised intelligence tests in adults with CHD. This study assesses the cognitive function in Fontan patients compared with acyanotic CHD patients whether restrictions in cognitive function are present in adulthood and its association with health-related quality of life. Methods: Forty-four adult CHD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…The absence of a significant correlation between cognitive abilities and child‐reported QoL might indicate the complexity of children's self‐perception and expression regarding their well‐being in the context of a health condition like CHD. A recent study by Remmele et al (2023) showed also no association between cognitive function and self‐reported QoL in adults with CHD. It has been suggested that “relying solely on self‐reports of patients with CHDs might underestimate the severity of their challenges, at least in the domain of executive functions” (Bellinger et al, 2014, p. 9).…”
Section: Discussionmentioning
confidence: 92%
“…The absence of a significant correlation between cognitive abilities and child‐reported QoL might indicate the complexity of children's self‐perception and expression regarding their well‐being in the context of a health condition like CHD. A recent study by Remmele et al (2023) showed also no association between cognitive function and self‐reported QoL in adults with CHD. It has been suggested that “relying solely on self‐reports of patients with CHDs might underestimate the severity of their challenges, at least in the domain of executive functions” (Bellinger et al, 2014, p. 9).…”
Section: Discussionmentioning
confidence: 92%